Human Gait Analysis Using Inertial Measurement Unit for Rehabilitation - Han, Yi Chiew (Curtin University, 2019)
The main contribution is an Inertial Measurement Units (IMUs) based system that classifies a selection of gait anomalies to assist the clinicians in diagnosis of walking disorders. The developed 3-D angle and stride length estimation algorithms have been validated against gold standard Vicon optical motion capture system. The proposed IMU-based gait phase detection method has also been validated against force sensors. Additionally, IMU and video synchronization provides numerical data to the clinicians for visual inspection.